PENGARUH METODE FERMENTASI SUBSTRAT PADAT DAN SUBSTRAT TERENDAM PADA BIJI SORGUM TERHADAP KUALITAS TEPUNG - Erni Sofia Murtini; M. Iqbal Prawira-Atmaja; Aji Sutrisno (Jurnal Teknologi dan Industri Pangan, 2016)
The utilization of sorghum as food products is restricted by its lack of digestibility and the presence of anti-nutrients factors. Fermentation process has been recommended to improve cereal-based flour quality. This study was aimed to evaluate the effect of two fermentation methods namely solid state (a method adopting tempeh processing procedure with fermentation course of 60 and 72 h) and submerged fermentation (similar to ampok processing procedure with fermentation course of 72 and 84 h). The fermented-sorghum grains were then dried, and milled to produce sorghum flour. Analyses of proximate, physical poperties (particle size index/PSI, Water Absorption Index/WAI, swelling power) and amylograph profiles were carried out to obtain the flour characteristics. The results showed that both fermentation methods significantly influenced the proximate, physical and amilograph properties of the sorghum flour.  Solid state fermentation of sorghum grains decreased the starch content, reduced its lightness, swelling power and viscosity, while increased the PSI and WAI. However, the solid state fermentation did not significantly change the protein, fat, ash and moisture content of the sorghum flour. Submerged fermentation of sorghum grain decreased the starch and protein content, increased the lightness, swelling power and viscosity, while did not significantly modify fat, ash and moisture content of the flour. Based on the characteristics obtained, it is suggested that sorghum flour made from solid state fermented-sorghum grain may be applicable for making–not viscous-food products, such as porridge. On the other side, the sorghum flour made from submerged-fermented-sorghum grain may be used as thickening agent, binder or for making highly viscous food products.